Effects on the Perceptions of Language Importance in Canada’s Urban Indigenous Peoples - Eva M Jewell (aboriginal policy studies, 2016)
The following analysis utilizes data drawn from the 2012 Aboriginal Peoples Survey (APS) to examine the effects of age, sex, education, household type, and exposure to Indigenous[1] language inside the home and outside the home on the perceived importance of Indigenous language for Indigenous people living in urban centres across Canada. The results of the regression analysis indicate that “exposure to Indigenous language inside the home” and “exposure to Indigenous language outside the home” is directly related to how important Indigenous language is perceived by urban Indigenous peoples. [1] Statistics Canada and the Government of Canada utilize the term “Aboriginal” to identify First Nations, Metis, and Inuit peoples. The author has chosen to use “Indigenous”, a term that communicates the quality of being original in land and place.